Ethnic education and language Koreans in China as a factor in the maintenance of ethnic diversity and inter-ethnic communication - Yem, N (Journal of Oriental Studies, 2016)
The national policy of China towards ethnic minorities is based on two factors. On the one hand it is based make up the imperial tradition of national relations and internal management, which were characterized by national unity and paternalism. On the other hand - the communist ideology of citizenship based on equal treatment of ethnic groups, as well as the cultivation of a single nation, the purpose of which is to create a common identity. Raising the level of education of the Korean community in China is often a good example in many studies as an academic and journalistic nature. While maintaining a strong sense of ethnic identity, the Korean diaspora in China has reached a high level of education compared to other national minorities. The education system in the environment of the Korean community in China, as in the whole of China, faced with the problem of bilingualism. The government has a policy of systematic increase in the use of Chinese language among the ethnic minorities. The practice of bilingual education of ethnic groups weakened. Despite the peculiarities of language situation of Chinese Koreans in the changed circumstances of the modern period, it is noted that they are well preserved their language.